Exploring the effectiveness of STEAM design processes on middle school students' creativity - Ozkan, Gulbin; Topsakal, Unsal Umdu (SPRINGER, 2021)
Creativity has an important role in many scientific processes which constitute a large and complex structure. It is difficult to identify and measure. Students' creativity can be enhanced through specific education programs. The aim of this study was to develop a science, technology, engineering, art, mathematics (STEAM) design process program for teaching 7th grade middle school students to enhance their verbal and figural creativity. The study lasted 11 weeks. Pre-test/post-test quasi-experimental method with a nonequivalent control group was used. Study Group (n = 34) was presented a teaching approach focused on STEAM education, while the control group (n = 34) was taught based on the science curriculum and science textbook. Nine different STEAM design activities were developed. The data were collected with the Torrance Test of Creative Thinking. The SPSS Program was used in analyzing the data. At the end of the study, significant differences were determined in favor of the study group in both verbal and figural creativity. As a result of the study, recommendations for implementation of STEAM design processes were discussed.
Keywords: Creativity; Creative thinking; Design; STEAM; STEM; TORRANCE TESTS; EDUCATION; SCIENCE; ART; TECHNOLOGY; THINKING; Education & Educational Research; Engineering